Edukasi Kesehatan tentang Dengue Hemorrhagic Fever sebagai Upaya Pencegahan DBD pada Remaja SMK PGRI 1 Cimahi - Theophylia Melisa Manumara; Gandung Galih Asmoro; Chania Marsela Mandani Putri; Euis Nur Asy-syifa Najiah; Vika Rahmanisah; Bunga Elia; Rita Juwita (Jurnal Medika: Medika, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health concern in Indonesia, including in Cimahi City, where cases increased notably in early 2024. Transmission of the dengue virus through Aedes aegypti mosquitoes commonly affects adolescents who spend considerable time in school environments. Health education serves as a key strategy to enhance students’ knowledge and awareness regarding DHF prevention. This community service activity aimed to provide comprehensive education to students of SMK PGRI 1 Cimahi about the causes, symptoms, transmission, and prevention of DHF through the 3M Plus strategy. The method used in this service activity is an interactive method to measure knowledge improvement. The results indicated a significant increase in students’ understanding of vector characteristics, early warning signs of DHF, and preventive actions applicable at school and home. School-based health education proved effective in shaping positive health behaviors among adolescents and supporting efforts to reduce DHF incidence within the community. The outcomes of this activity include the preparation of a scientific publication and intellectual property registration.